2004
DOI: 10.1021/bi035966c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hydrophobic Interactions between Proteins and Lipids:  Free Fatty Acids Activate Phospholipase C δ1 via Allosterism

Abstract: Lipids are well recognized ligands that bind to proteins in a specific manner and regulate their function. Most attention has been placed on the headgroup of phospholipids, and little is known about the role of the acyl chains in mediating any effects of lipids on proteins. In this report, free fatty acids (FFA) were found to bind and activate phospholipase C delta1(PLC delta1). The unsaturated FFA arachidonic acid (AA) and oleic acid were able to stimulate PLC delta1 up to 30-fold in a dose-dependent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…Unlike the role of EF-hands in other host proteins, the EF-hands of PLCs do not undergo Ca 2+ -dependent conformational changes. There are data suggesting that the EF-hands of PLC-δ1 bind specifically to fatty acids and that this binding stimulates the catalytic activity of the enzyme, implying that PLCs may be sensitive to the nature of the hydrocarbon chains [44,45]. Although the crystal structure shows limited contact between the EF hands and the catalytic domain, their role in the regulation of the enzyme either directly or through interaction with other proteins or cofactors remains to be seen.…”
Section: Elongation Factor (Ef) Handsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the role of EF-hands in other host proteins, the EF-hands of PLCs do not undergo Ca 2+ -dependent conformational changes. There are data suggesting that the EF-hands of PLC-δ1 bind specifically to fatty acids and that this binding stimulates the catalytic activity of the enzyme, implying that PLCs may be sensitive to the nature of the hydrocarbon chains [44,45]. Although the crystal structure shows limited contact between the EF hands and the catalytic domain, their role in the regulation of the enzyme either directly or through interaction with other proteins or cofactors remains to be seen.…”
Section: Elongation Factor (Ef) Handsmentioning
confidence: 99%
“…This peptide was therefore defined as the signal transfer region of Gβ. Extensive studies with other peptides identified a second signal transfer region (Gβ [42][43][44][45][46][47][48][49][50][51][52][53][54] ) in the seventh blade of Gβ, and revealed segments in the second, fifth and seventh blade that hold the Gβγ/PLC-β2 complex together during activation ( Figure 5) [67,68]. In addition, it was found that the geranylgeranylated moiety attached to the C-terminal segment of the Gγ, which is proximal to the membrane and anchors Gβγ to lipids, binds to the PLC-β2 [69,70].…”
Section: Plc-β2 Binding Site(s) In Gβγmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated EF-hand domain of PLC ␦1 has previously been expressed and shown to interact with free fatty acids (13,14). To further explore its binding partners, interaction of rEF with various phospholipid species was examined by a centrifugation-filtration vesicle binding assay.…”
Section: Isolated Ef-hand Domain Of Plc ␦1 Binds To Anionic Phospholimentioning
confidence: 99%
“…Based on the structural similarities between the PLC ␦1 EF-hand and other calcium-binding EF-hand proteins such as calmodulin, it has been suggested that the EF-hand domain of PLC ␦1 might serve a regulatory role through calcium binding. Elsewhere, interactions of the EF-hand domain with free fatty acids have also been suggested (13,14). Additionally, numerous EF-hand motif-containing proteins have been reported to be involved in lipid binding.…”
mentioning
confidence: 99%